Endoglin expression level discriminates long-term hematopoietic from short-term clonogenic progenitor cells in the aorta - ROQUES, Marion; DURAND, Charles; GAUTIER, Rodolphe; CANTO, Pierre-Yves; PETIT-COCAUL, Laurence; YVERNOGEAU, Laurent; DUNON, Dominique; SOUYRI, Michèle; JAFFREDO, Thierry (Haematologica (Roma), 2012)
CD105 is an auxiliary receptor for the transforming growth factor beta superfamily, highly expressed on proliferating endothelial cells and adult hematopoietic stem cells. Because CD105 mRNA expression was reported in the developing aortic region, we further characterized its expression profile in the aorta and examined the hematopoietic potential of CD105(+) cells. Aortic endothelial cells, intra-aortic hematopoietic cell clusters and the purified cell fraction enriched in progenitor/hematopoietic stem cell activity expressed CD105. Aortic hematopoietic short-term clonogenic progenitors were highly enriched in the CD105(intermediate) population whereas more immature long-term progenitors/hematopoietic stem cells are contained within the CD105(high) population. This places CD105 on the short list of molecules discriminating short-term versus long-term progenitors in the aorta. Furthermore, decreasing transforming growth factor beta signaling increases the number of clonogenic progenitors. This suggests that CD105 expression level defines a hierarchy among aortic hematopoietic cells allowing purification of clonogenic versus more immature hematopoietic progenitors, and that the transforming growth factor beta pathway plays a critical role in this process.